Bioconversion of lignocellulosic substrates for the production of polyhydroxyalkanoates. (September 2020) - de Souza, Larissa; Y., Manasa; Shivakumar, Srividya
Abstract: Lignocellulose, the most abundant and renewable carbon resource, is untapped due to its protective lignin shield. Biological pretreatment employs white rot fungi (WRF) to remove lignin and expose the cellulose/hemicellulose layers for exploitation. The present work was conducted to explore the possibility of biologically pretreating lignocellulose with WRF and using the sugars, liberated from this process, as renewable and inexpensive feedstock for the production of polyhydroxyalkanoates (PHA). Pleurotus ostreatus MTCC 142 (P142) was used to bring about bio-delignification of lignocellulose under solid state fermentation (SSF) conditions. The hydrolysates thus obtained were used for bioconversion to PHA, using Bacillus megaterium Ti3 under submerged fermentation (SmF) conditions in a nitrogen-deficient medium. From the lignocellulosic substrates used, the highest sugar yields, post bio-delignification, were obtained from corn husk (6 mg/mL). Production of PHA from pure sugars revealed a preference for xylose with 50% PHA accumulation. The pretreated corn husk (CH) hydrolysate yielded 1 g/L PHB with an accumulation of 57.8% after 48 h, comparable to that obtained using xylose based medium and significantly higher ( p  < 0.05) than the PHA accumulation (45.7%) obtained from the glucose medium. Fermentation kinetics revealed that PHB yield obtained from the hydrolysate was 3 fold higher than glucose-based production. Similarly, PHB yield, in terms of substrate conversion Yp/s (gPHA /gS ), also increased 2 folds in the case of biologically pretreated lignocellulosic bioconversion to PHB. Characterization of the polymer through Proton ( 1 H) and Carbon ( 13 C) NMR analyses revealed that it was the short-chain-length (scl) polyester, poly-β-hydroxybutyrate (PHB). Highlights: Eco-friendly biological pretreatment of waste lignocellulose using white rot fungi, Pleurotus ostreatus MTCC 142 Generation of sugar feedstocks through biologically pretreated waste lignocellulose as renewable carbon resources. Production by Bacillus megaterium Ti3 yielded 57.8% PHA accumulation from hydrolysates of biologically pretreated corn husk NMR analysis revealed that the polymer was poly-β-hydroxybutyrate (PHB).